Computational intelligence concepts to implementations - Eberhart, Russell C.; Shi, Yuhui (San Francisco : Morgan Kaufmann Publishers, 2007)
Russ Eberhart and Yuhui Shi have succeeded in integrating various natural and engineering disciplines to establish Computational Intelligence. This is the first comprehensive textbook, including lots of practical examples.-Shun-ichi Amari, RIKEN Brain Science Institute, Japan This book is an excellent choice on its own, but, as in my case, will form the foundation for our advanced graduate courses in the CI disciplines.-James M. Keller, University of Missouri-Columbia The excellent new book by Eberhart and Shi asserts that computational intelligence rests on a foundation of evolutionary computation. This refreshing view has set the book apart from other books on computational intelligence. The book has an emphasis on practical applications and computational tools, which are very useful and important for further development of the computational intelligence field.-Xin Yao, The Centre of Excellence for Research in Computational Intelligence and Applications, Birmingham The soft analytic tools that comprise the field of computational intelligence have matured to the extent that they can, often in powerful combination with one another, form the foundation for a variety of solutions suitable for use by domain experts without extensive programming experience. Computational Intelligence: Concepts to Implementations provides the conceptual and practical knowledge necessary to develop solutions of this kind. Focusing on evolutionary computation, neural networks, and fuzzy logic, the authors have constructed an approach to thinking about and working with computational intelligence that has, in their extensive experience, proved highly effective. Features Moves clearly and efficiently from concepts and paradigms to algorithms and implementation techniques by focusing, in the early chapters, on the specific concepts and paradigms that inform the authors methodologies. Explores a number of key themes, including self-organization, complex adaptive systems, and emergent computation. Details the metrics and analytical tools needed to assess the performance of computational intelligence tools. Concludes with a series of case studies that illustrate a wide range of successful applications. Presents code examples in C and C++. Provides, at the end of each chapter, review questions and exercises suitable for graduate students, as well as researchers and practitioners engaged in self-study. Makes available, on a companion website, a number of software implementations that can be adapted for real-world applications. Moves clearly and efficiently from concepts and paradigms to algorithms and implementation techniques by focusing, in the early chapters, on the specific concepts and paradigms that inform the authors' methodologies. Explores a number of key themes, including self-organization, complex adaptive systems, and emergent computation. Details the metrics and analytical tools needed to assess the performance of computational intelligence tools. Concludes with a series of case studies that illustrate a wide range of successful applications. Presents code examples in C and C++. Provides, at the end of each chapter, review questions and exercises suitable for graduate students, as well as researchers and practitioners engaged in self-study. Makes available, on a companion website, a number of software implementations that can be adapted for real-world applications.
Includes bibliographical references and index.
Keywords: Computational intelligence; Neural networks (Neurobiology); Electronic books